2022
DOI: 10.1177/09544119211069207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plate contouring quality on the biomechanical performance of high tibial osteotomy fixation: A parametric finite element study

Abstract: Locking plates have threaded holes, in which threaded-head screws are affixed. Hence, they do not need to be in intimate contact with underlying bone to provide fixation. There are, however, reports that a large distance between the plate and the bone might cause clinical complications such as delayed union or nonunion, screw pull out, and screw and plate breakage. Considering the diversity in the capabilities and costs of different plate customization techniques, the purpose of this study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…With the gradual opening of the osteotomy gap, the horizontal distance between the proximal fragments, distal fragments, and the bone-plate clearance increase correspondingly (11,12,15). A bone-plate mismatch may increase the risk of implant failure from, for example, locking pin backout or screw breakage after tibial osteotomy (18)(19)(20).…”
Section: Importance Of Choosing the Hinge Point At The Lateral Part O...mentioning
confidence: 99%
See 4 more Smart Citations
“…With the gradual opening of the osteotomy gap, the horizontal distance between the proximal fragments, distal fragments, and the bone-plate clearance increase correspondingly (11,12,15). A bone-plate mismatch may increase the risk of implant failure from, for example, locking pin backout or screw breakage after tibial osteotomy (18)(19)(20).…”
Section: Importance Of Choosing the Hinge Point At The Lateral Part O...mentioning
confidence: 99%
“…The proper fitting of the plate to the bony surface is essential for the appropriate and effective delivery of physiological stress, which prevents a loss of fixation stability and plate fracture (13)(14)(15)26). Previous biomechanical studies have also revealed that a large clearance between the locking plate and the bone beneath the plate is associated with a greater concentration of stress at the construct, increased pressure at the lateral hinge, and weakened axial stiffness (27)(28)(29).…”
Section: Additional Procedures May Be Essential For Cases With Large ...mentioning
confidence: 99%
See 3 more Smart Citations